Hindfoot alignment at one year after total knee arthroplasty - Takenaka, Takashi (Knee Surg Sports Traumatol Arthrosc, 2015)
PURPOSE: It has previously been found that valgus hindfoot alignment (HFA) improves 3 weeks following total knee arthroplasty (TKA) for varus knee osteoarthritis (OA). In the present study, HFA was evaluated prior to TKA, as well as 3 weeks and 1 year following TKA. Using these multiple evaluations, the chronological effects of TKA on HFA were investigated. METHODS: The study included 71 patients (73 legs) who underwent TKA for varus knee OA. Radiograph examinations of the entire limb and hindfoot were performed in the standing position prior to TKA, as well as 3 weeks and 1 year following TKA. The varus–valgus angle was used as an indicator of HFA in the coronal plane. Patients were divided into two groups according to the preoperative varus–valgus angle: a hindfoot varus group (varus–valgus angle <76°) and a hindfoot valgus group (varus–valgus angle ≥76°). The changes in the varus–valgus angle were evaluated and compared in both groups. RESULTS: In the hindfoot valgus group, the mean ± standard deviation varus–valgus angle significantly declined from 80.5 ± 3.1° prior to TKA to 78.6 ± 3.7° 3 weeks following TKA and 77.1 ± 2.7° 1 year following TKA. However, in the hindfoot varus group, the mean varus–valgus angle prior to TKA (72.7 ± 2.6°) did not differ significantly from the mean varus–valgus angles 3 weeks (72.3 ± 3.3°) or 1 year (73.5 ± 3.0°) following TKA. CONCLUSIONS: HFA improved chronologically in legs with hindfoot valgus as a result of the alignment compensation ability of the hindfoot following TKA. However, no improvement was noted in legs with hindfoot varus because the alignment compensation ability of the hindfoot had been lost. The patients with hindfoot varus should be attended for ankle pain in the outpatient clinic after TKA. LEVEL OF EVIDENCE: III.